Loss reduction via load balancing single phase versus three phase connectivity - Khan Sheroz (2023)
Electric load management with single and three phases was analyzed as per customer requirements. The electric losses of unbalanced networks were calculated. Balancing of three phase saved the electric energy and optimized usages. Single phase connectivity for residential consumers was found preferable in all contexts.